Vanillin isotopic intramolecular 13C profile through polarization transfer NMR pulse sequence and statistical modelling. (December 2021) - Portaluri, Vincent; Thomas, Freddy; Jamin, Eric; Lorandel, Benjamin; Silvestre, Virginie; Akoka, Serge; Remaud, Gérald S.
Abstract: Vanilla is the most popular aroma among consumers and the authentication of its main compound – vanillin – remains a current challenge in transformed products, whose low vanillin concentration is a limitation to SNIF-NMR use. A new and fast NMR-isotopomics approach is proposed with modified INEPT 13 C NMR pulse sequence implemented for vanillin intramolecular composition determination. Position-specific isotopic compositions were estimated through statistical modelling from incomplete experimental data (since quaternary carbons did not benefit from polarization transfer), allowing the comparison of databases analyzed either with single pulse or multipulse method. The new approach was validated: a sensitivity gain was achieved while preserving performances similar to reference method. Vanillin ex-C4 -sugars, a growing source in the market, was described and blends with biosynthesized vanillin were positively discriminated from vanillin ex-beans, the main adulteration target. The method was applied on vanilla sugars to demonstrate its applicability for convenience good authentication. Vanillin quantity required for analysis was reduced to 50 mg, opening path to new control possibilities in finished food products. Graphical abstract: Image 1 Highlights: INEPT pulse was validated for vanillin authentication to improve sensitivity. Isotopic parameters were modelled with apparent partial ones from INEPT method. Vanillin ex-C4 sugars and its potential for advanced fraud was evaluated. Vanilla sugars were investigated using the developed method.